The flavonoid 4,4'-dimethoxychalcone promotes autophagy-dependent longevity across species - Carmona-Gutierrez, Didac; Zimmermann, Andreas; Kainz, Katharina; Pietrocola, Federico; Chen, Guo; Maglioni, Silvia; Schiavi, Alfonso; Nah, Jihoon; Mertel, Sara; Beuschel, Christine B; Castoldi, Francesca; Sica, Valentina; et al. (Nature communications, 2019)
Ageing constitutes the most important risk factor for all major chronic ailments, including malignant, cardiovascular and neurodegenerative diseases. However, behavioural and pharmacological interventions with feasible potential to promote health upon ageing remain rare. Here we report the identification of the flavonoid 4,4'-dimethoxychalcone (DMC) as a natural compound with anti-ageing properties. External DMC administration extends the lifespan of yeast, worms and flies, decelerates senescence of human cell cultures, and protects mice from prolonged myocardial ischaemia. Concomitantly, DMC induces autophagy, which is essential for its cytoprotective effects from yeast to mice. This pro-autophagic response induces a conserved systemic change in metabolism, operates independently of TORC1 signalling and depends on specific GATA transcription factors. Notably, we identify DMC in the plant Angelica keiskei koidzumi, to which longevity- and health-promoting effects are ascribed in Asian traditional medicine. In summary, we have identified and mechanistically characterised the conserved longevity-promoting effects of a natural anti-ageing drug.
Keywords: rostlinné extrakty; Animals; Caenorhabditis elegans; Humans; Plant Extracts; transkripční faktory GATA; myši inbrední C57BL; Cell Line; mužské pohlaví; Gene Expression Regulation; Longevity; Cell Death; transkripční faktory; Medicine, East Asian Traditional; Signal Transduction; Mice, Inbred C57BL; Drosophila melanogaster; Autophagy; stárnutí; Transcription Factors; Angelica; Male; buněčné linie; proteiny přenášející kationty; signální transdukce; tradiční orientální medicína; Saccharomyces cerevisiae - proteiny; zvířata; ischemická choroba srdeční; Saccharomyces cerevisiae Proteins; myši; autofagie; Cation Transport Proteins; regulace genové exprese; lidé; dlouhověkost; buněčná smrt; flavonoidy; Flavonoids; Mechanistic Target of Rapamycin Complex 1; sirolimus; Saccharomyces cerevisiae; Sirolimus; Mice; GATA Transcription Factors; mTORC1; Myocardial Ischemia; Aging